Program Employee Relations PT TELKOM INDONESIA: Kids Go To Office - Syuderajat, Fajar; Prameswari, Yoke Putri (Universitas Semarang, 2017)
Backed by Telkom who want to make a good relationship with employees and their families so decided to create Kids Go To Office event. Aims to know the research and listening, planning and decision, communicating and implementing (communication and action), and evaluation (evaluation) of Kids Go To Office activities. The method used in this research is descriptive method. Data obtained through observation, interview, and literature study. The result is in conducting research and listening, Telkom has conducted an interview to find out what the prospective participants want. At the planning and implementation stage, Telkom is doing very well because it is almost in accordance with the flow and the existing stage. In addition, at the stage of communication and implementation went well because the enthusiastic participants are so great. While at the evaluation stage, Telkom has not done well seen from the absence of measuring instrument or indicator of success.